2005
DOI: 10.1021/es050642s
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Resuspended Soil in Lead Flows in the California South Coast Air Basin

Abstract: The inputs and outputs of airborne lead in the South Coast Air Basin of California (SOCAB) are quantified according to standard mass balance calculations. Results for 2001 show that approximately 49,000 kg of lead exitthe Basin each year, but traditional sources contribute only about 6500 kg of lead each year. We resolve this discrepancy through a simple computer model that quantifies the resuspension of lead-containing particles. Our results suggest that these lead particles were deposited during the years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
51
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 18 publications
5
51
0
Order By: Relevance
“…The slope of the least squares fit for zinc to Cl, together with standard error of fit, were used as a fingerprint for this source (Table 11). Bangladesh from 1999, Pb may come from fugitive sources, for examples paint and pigment, Pb acid battery (Begum et al, 2005b), or the resuspended soil dust (Harris et al, 2005). Since Pb does not have any strong association with other elements, it is not possible to create a multi-elemental fingerprint for this source.…”
Section: Zinc-source Fingerprintmentioning
confidence: 99%
“…The slope of the least squares fit for zinc to Cl, together with standard error of fit, were used as a fingerprint for this source (Table 11). Bangladesh from 1999, Pb may come from fugitive sources, for examples paint and pigment, Pb acid battery (Begum et al, 2005b), or the resuspended soil dust (Harris et al, 2005). Since Pb does not have any strong association with other elements, it is not possible to create a multi-elemental fingerprint for this source.…”
Section: Zinc-source Fingerprintmentioning
confidence: 99%
“…6,7,43 Temporal variations of the isotopic composition of leaded gasoline in California correspond with temporal differences in ores used to manufacture alkyl-lead in the U.S. during that period. In the 1960s, the ores were obtained primarily from Australia, Canada, Mexico, and Peru, which had 44 It is, therefore, assumed that the isotopic composition of those aerosols reflects a mixture of contemporary and previous industrial lead emissions that have been resuspended, as observed in Los Angeles 8 and the San Francisco Bay area. 47 showed a significant correlation (r = 0.76, p < 0.001, n = 34) between wildfire frequency and regional spring and summer temperatures in the Western U.S.…”
mentioning
confidence: 99%
“…Although industrial lead exposures have declined over the past three decades with the elimination of leaded petrol, as they have elsewhere (Annest et al, 1983), the environmental legacy from those emissions remain a source of potential exposure (Harris and Davidson, 2005;Laidlaw et al, 2012). Moreover, recent studies have determined that relatively low blood lead levels that were previously considered innocuous have been associated with adverse human health problems (ACCLPP, 2012;Lanphear et al, 2005).…”
Section: Introductionmentioning
confidence: 99%